If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y/3+11=y/2-2
We simplify the equation to the form, which is simple to understand
y/3+11=y/2-2
Simplifying:
+ 0.333333333333y+11=y/2-2
Simplifying:
+ 0.333333333333y+11=0.5y-2
We move all terms containing y to the left and all other terms to the right.
+ 0.333333333333y-0.5y=-2-11
We simplify left and right side of the equation.
-0.166666666667y=-13
We divide both sides of the equation by -0.166666666667 to get y.
y=78
| 8-8x=208-43x | | 1546-5x=5x+16 | | 2x+6=-54-8x | | 138-4x=5x+12 | | 3x+84=8x+9 | | 4(8a-5)-[3(2a-2)+5]= | | 37-6x=3x+18 | | 62-2x=13-7x | | 4x+28=14x-52 | | (3x+84)(8x+9)= | | 3x^2+2x-17=0 | | 3x^2+2x-17=y | | 4x+28=14x+52 | | 3x-4z=12 | | y=(y-6) | | 15y-56=13y | | 2x+6=-4 | | -180-8x=24-17x | | (4x+30)(6x+6)= | | 2r+6s-6(7r-9s)= | | (7+u)(3u-4)=0 | | 6x^2=21x-9 | | 8-10x=16x+23 | | 6x+21=15x-69 | | 3a^2-n+4b^2=(3a-2b)(a-2b) | | r^2=10-3r | | 6x+21=15x-56 | | (4w-7)(2-w)=0 | | 3a+20=4a+k | | 2(6v-1)= | | (7-z)(3z+8)=0 | | -2x-108=45+7x |